PENGARUH KECEPATAN GERAK DAN DAYA PEMANCAR PADA MESIN PENGERING KAYU YANG MENGGUNAKAN GELOMBANG MIKRO - Darmawan Utomo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
Conventional wood drying by the method of using hot air as a heating agent have a major weakness, it takes a long time to completely dry some wood. Usages of microwave as a wood dryer are commonly fast, but the device available in the market are not suitable for Indonesian wood characteristics. There for a prototype of microwave driven wood dryer has been built with the emitting power of two 800 watts microwave transmitter, adjustable power output, using conveyor as feeder with adjustable speed. The machine has been tested to do some research on the impact of giving speed and giving power of 100, 80 and 60 percent on local wood, such as Teak, Mahogany and Cedar wood. The wood samples that is used has a measurement of height is 2,5 cm and 5 cm, wide 5 cm, and length of 25 cm and 50 cm. From the experiment, a result has been archived that movement speed affect average evaporation speed per microwave transmitter, for Teak, Mahogany and Cedar is in corresponding order, is 4.09, 5.22 and 3.32 grams/minutes (on 100 percent power), 3.18, 4.45 and 3.56 grams/minutes (on 80 percent power) and 2.98, 3.98 and 3.32 grams/minutes (on 60 percent power). From the water evaporation value can be concluded that in order to evaporate 1 kg water from Teak wood, it requires 4 kWh of energy at 100 percent power outage.